A Survey on Gurukul Education System - PAREEK, DR. ADITYA (The journal of contemporary issues in business and government, 2021)
Since ancient times India have always exaggerate of the rich tradition in the field of education and learning. It is well acknowledged that peoples from other countries like Europe, Middle East & Portugal came to India to obtain a quality of education. The anciently implemented popular education systems in India was The Gurukul Method. The topics learned differed from Sanskrit to Scriptures to Logic and Metaphysics, and the gained wisdom would be passed down through the generations. However, during the Colonial period this system was introduced when the British established schools that accompanied a curriculum limited to subjects such as mathematics, science etc. While the old system included more contact with nature, the new program was directed more towards school. Activities like yoga, meditation, singing etc. developed and equipped positivity and satisfaction. Often, it was obligatory to do regular chores on their own with a desire to communication practical knowledge. All of these have helped in development of persona & increased confidence, intellect, sense of discipline and awareness that is required to face the real world that lies ahead even today. This paper discloses about the Gurukul schooling method and its difference to modern schooling.